„PO ILU PATYKACH ZANIKA ETYKA?” O POLITYCZNYCH I METAFIZYCZNYCH HORYZONTACH EPIGRAMATYKI WACŁAWA KLEJMONTA - Żurawlew, Tomasz (Acta Neophilologica, 2012)
The present paper aims at an analysis of the axiological paradigm in the satirical output of Wacław Klejmont, a poet, essayist and literary critic, locally well known in the culture of the Polish Warmia and Masuria. The author attempts to set a broader context of the epigrams and specifically focuses on their theological aspects that have not yet been so well exposed in the Polish aphoristic literature.